Importance of central AT1 receptors for sodium intake induced by GABAergic activation of the lateral parabrachial nucleus - Roncari, C. F. [UNESP]; David, R. B. [UNESP]; Paula, Patricia Maria de [UNESP]; Colombari, Débora Simões de Almeida [UNESP]; de Luca, L. A. [UNESP]; Menani, José Vanderlei [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
The blockade of the inhibitory mechanisms for sodium intake with GABAergic activation in the lateral parebrachial nucleus (LPBN) induces strong ingestion of water and hypertonic NaCl in satiated and normovolemic rats. A question that remains is if the activity of facilitatory mechanisms, like angiotensin II, is necessary for sodium and water intake induced by muscimol (GABA(A) receptor agonist) injected into the LPBN. Therefore, in the present study, we investigated the effects of the blockade of angiotensinergic AT(1) receptors with losartan injected i.c.v. on 0.3 M NaCl and water intake induced by muscimol injected into the LPBN in satiated and normovolemic rats. Male Holtzman rats with stainless steel cannulas implanted bilaterally into the LPBN and unilaterally into the lateral ventricle were used. Bilateral injections of muscimol (0.5 nmol/0.2 mu l) into the LPBN combined with i.c.v. injection of vehicle induced 0.3 M NaCl (31.7 +/- 1.8 ml/240 min, vs. saline: 0.4 +/- 0.3 ml/240 min) and water intake (21.5 +/- 1.9 ml/240 min, vs. saline: 0.8 +/- 0.2 ml/240 min). Losartan (50 and 100 mu g/1.0 mu l) injected i.c.v. reduced the effects of LPBN-muscimol on 0.3 M NaCl (18.9 +/- 1.9 and 9.9 +/- 1.7 ml/240 min, respectively) and water intake (9.8 +/- 1.7 and 5.1 +/- 1.1 ml/240 min, respectively). The results suggest that the activation of central AT(1) angiotensinergic receptors is essential for hypertonic NaCl and water intake induced by the blockade of the inhibitory mechanisms with muscimol injected into the LPBN in satiated and normovolemic rats. (C) 2011 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: sodium appetite; parabrachial nucleus; angiotensin II; satiety; GABA